Nonsmooth Optimal Value and Policy Functions in Mechanical Systems Subject to Unilateral Constraints - Banjanin, Bora S.; Burden, Samuel A. (IEEE control systems letters, 2020)
State-of-the-art approaches to optimal control use smooth approximations of value and policy functions and gradient-based algorithms for improving approximator parameters. Unfortunately, we show that value and policy functions that arise in optimal control of mechanical systems subject to unilateral constraints - i.e., the contact-rich dynamics of robot locomotion and manipulation - are generally nonsmooth due to the underlying dynamics exhibiting discontinuous or piecewise-differentiable trajectory outcomes. Simple mechanical systems are used to illustrate this result and the implications for optimal control of contact-rich robot dynamics.